ELEMENTS OF ISLAMIC HISTORY IN THE WORKS OF NUR AL-DIN AL-RANIRI - Hamzah, Norhayati; Mohd Noor, Arba’iyah; Denisova, Tatiana (Journal of Al-Tamaddun, 2017)
Al-Raniri (d. 1658) was a renowned and versatile scholar of Aceh during the rule of Sultan Iskandar Thani (1046-1050 AH/1636-1641 AD). He had authored 35 works on various disciplines of Islam specifically on tasawuf, theology, fiqh and history. The importance of history to al-Raniri is manifested not only in his largest work of history entitled Bustan al-Salatin fi Dhikr al-Awwalin wa al-Akhirin (known as Bustan) but also in numbers of his other works. Many scholars such as Voorhoeve, Winstedt, Drewes and Braginsky confine al-Raniri’s work on history to Bustan. However, based on the content analysis of al-Raniri’s works, the authors emphasize that there are actually six historical works of al-Raniri including Bustan that contains the element of Islamic history. Therefore, this article attempts to reveal al-Raniri’s works on history and the element of Islamic history in his other masterpieces. It employed a qualitative research approach that entails the technique of documentation in collecting data while inductive approach to content analysis was utilized for data analysis. The main documents used were the three versions of the manuscript of Bustan (Raffles Malay 8, Raffles Malay 42 and UM 41). The outcome of this research reveals the element of Islamic history in other works of al-Raniri, indicates that history is the basic theoretical element of his works.